Pilocytic Astrocytoma of the Left Cerebellar Hemisphere with Obstructive Hydrocephalus in A Pediatric Patient: A Case Report - Pannamareddy, Harshitha Reddy; Aafreen, Shaik Uzma; Prattipati, Beulah (Journal of Pharmacy Practice and Community Medicine)
Pilocytic astrocytoma is a World Health Organization (WHO) Grade I glioma commonly affecting children and adolescents, with the cerebellum being the most frequent site of involvement. These tumors often present with features of raised intracranial pressure due to obstruction of cerebrospinal-fluid pathways. We report a case of a 14-year-old female who presented with headache, recurrent vomiting, giddiness, and sudden episodes of fall. Neuroimaging revealed a solid cystic lesion in the left cerebellar hemisphere causing compression of the fourth ventricle and obstructive hydrocephalus. The patient underwent left suboccipital craniectomy with tumor decompression, and histopathological examination confirmed pilocytic astrocytoma. Postoperative recovery was favorable, with complete resolution of presenting symptoms. This case highlights the importance of early diagnosis, timely surgical intervention, and the critical role of clinical pharmacists in optimizing drug therapy, monitoring adverse effects, and improving patient outcomes in pediatric neuro-oncology cases.
Keywords: Cerebellar tumor; Pediatric brain tumor; Pharmacy practice; Pilocytic astrocytoma